New species and a new genus of non-marine ostracods (Crustacea, Ostracoda) in the upper Barremian (Lower Cretaceous) of the Cuenca Ranges, Central Spain - Marta Díez-Somolinos; Benjamin Sames; Mélani Berrocal-Casero; Fernando Barroso-Barcenilla (Cretaceous Research, 2026)

First insights into the role of evolutionary history in shaping venom composition of Vipera ammodytes - Margareta Lakušić; Costanza Piccoli; Marko Anđelković; Kostadin Andonov; Ivona Burić; José Carlos Brito; Angel Dyugmedzhiev; Saudin Merdan; Lennart Schmid; Elias Tzoras; Benjamin Florian-Hempel; Fernando Martínez-Freiría (Toxicon, 2026)

The diving katydid: A unique predator escape behavior in Ragoniella pulchella (Orthoptera: Tettigoniidae) - Charlie Woodrow; Benjamin C. Bluck; Fabio Sarria‐S; Lewis B. Holmes; Juan Sebastián Ulloa; Fernando Montealegre‐Z (Ecology, 2026)

Signal characteristics of potential airbursts in Titan’s atmosphere - Elisa Dong; Catherine D. Neish; John E. Moores; Shigeru Wakita; Gareth S. Collins; Peter G. Brown; Ralph D. Lorenz; Benjamin Fernando; Mark P. Panning (Icarus, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Characterizing canopy light penetration in black walnut (Juglans nigra) cultivars to inform selection for alley cropping - Benjamin Bishop; Fernando Torralbo; Nicholas A. Meier; Mark Coggeshall; Felix B. Fritschi; Ronald S. Revord (Agroforestry Systems, 2026)
Eastern black walnut ( Juglans nigra L.) is a nut-producing tree species that breaks dormancy late in the spring, allowing a winter alley crop to ripen before substantial canopy shade is formed. However, there is a high level of variation in the timing and structure of tree canopy development within the black walnut cultivar collection maintained at the University of Missouri Center for Agroforestry (UMCA). To identify cultivars with high levels of compatibility with winter alley cropping, we measured the amount of photosynthetically-active radiation transmitted (PARt) through the canopy. Eight physical traits were also measured to assess their relationship with light interception and to gain insight on characters that lead to greater understory light extinction. Significant differences between cultivars were seen in PARt, particularly on Julian date 132 (May 12) where a two-fold difference was observed in PARt between the most contrasting cultivars. Traits such as date of bud break, tree shape and live canopy ratio were associated with levels of PARt, providing preliminary support for strong component drivers of light displacement/penetration during spring. This study provides the first exploration of genetic variation in black walnut for above-ground compatibility with an understory crop, and in doing so, reports meaningful genetic variation exists for study and use. New context is reported for design of subsequent genetic, physiological, and plant-plant interaction studies. For example, there is not a negative relationship between leafing duration and fruit production, and late-leafing varieties, which are more suitable for agroforestry, remain productive in comparison to early-leafing ones. Additionally, these data may inform the selection or breeding of cultivars with improved complementary for alley cropping with winter grains, as well as management strategies (pruning) to improve light penetration in black walnut alley cropping systems.

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

New species of ostracods from the non-marine upper Barremian (Lower Cretaceous) of Vadillos-1 (Cuenca, Spain) - Marta Díez-Somolinos; Fernando Barroso-Barcenilla; Mélani Berrocal-Casero; Julio Rodríguez-Lázaro; Paloma Sevilla García; Benjamin Sames (Cretaceous Research, 2025)

Nutrients on the move: Investigating large scale fatty acid exports from European ponds via emerging insects - Lena Fehlinger; Fernando Chaguaceda; Pietro Tirozzi; Marina Tomás‐Martín; Ellinor Jakobsson; Teofana Chonova; Benjamin Misteli; Alberto Scotti; Jorge F. Henriques; Juan Rubio‐Ríos; Daniel Morant; Pierre Marle; et al. (Limnology and Oceanography, 2025)
Permanent ponds are key landscape units that supply various ecosystem services. Notably, the export of aquatic subsidies to land via emerging insects may significantly influence terrestrial food webs. Polyunsaturated fatty acids (PUFA), which enhance consumer fitness, are among the essential exported components. The patterns and drivers of dietary exports from ponds via insects remain poorly known, particularly at continental scales. We analyzed the exports of biomass, lipid, and fatty acid contents from emerging insects, sampled in 36 ponds across 11 European countries, from 36°N to 59°N and from 26°W to 19°E, over four seasons. We found that biomass and fatty acid exports decreased with increasing latitude and were higher in spring and summer. Seasonal effects also increased with higher latitudes. Temperature was the most important predictor of insect biomass, explaining 27.6% of the total variation and showing an unimodal response. Thus, increasing temperature may promote exports in colder regions and seasons but may negatively influence biomass exports in already warm regions. The exports of total lipids, PUFA, and eicosapentaenoic acid were correlated to exported biomass, while those of docosahexaenoic acid were linked to the emergence of Chaoboridae. Our findings indicated that PUFA contents were affected by taxonomic insect community composition and pond trophic state (indicated by chlorophyll a ). Two of the correlates identified here (temperature and trophic state) are influenced by anthropogenic activity via climate and land use change, respectively. Thus, human activity impacts the food webs in and around ponds by influencing the quantity and quality of nutritional exports.

Zonocypris goyi nov. sp. (Ostracoda) from the upper Barremian (Lower Cretaceous) of the Cuenca Range, Central Spain - Marta Díez-Somolinos; Benjamin Sames; Mélani Berrocal-Casero; Fernando Barroso-Barcenilla (Journal of Iberian Geology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Beyond sexual maturity: Importance of dietary changes in venom variation in Vipera ammodytes - Margareta Lakušić; Fernando Martínez-Freiría; Marko Anđelković; Benjamin-Florian Hempel (Toxicon, 2025)

Inter‐Laboratory Comparison of qPCR Assays for Piscirickettsia salmonis in Atlantic Salmon ( Salmo salar L.) in 11 Chilean Laboratories - Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner; Benjamin Diethelm‐Varela; Carla Anguita; Carlos Navarro Jerez; Fernando O. Mardones (Journal of Fish Diseases, 2025)
Real‐time PCR (qPCR) testing is an essential component of early detection surveillance systems for Piscirickettsia salmonis infection in Atlantic salmon farms in Chile. Currently, all 11 laboratories in the authorised diagnostic laboratory network use assays based on published protocols. Compared with other P. salmonis qPCR assays, these assays have the advantage of targeting two different genes, that is, the 16S ribosomal gene and the internal transcribed spacer (ITS), potentially allowing for higher diagnostic accuracy. However, variation and lack of harmonisation of qPCR testing systems (e.g., primers/probe, RNA/DNA as target, extraction methods, etc.) may contribute to among‐laboratory variation in qPCR results and an increased frequency of false‐negative and false‐positive results. The purpose of the ring trial reported herein was to compare qPCR results from 11 laboratories in Chile routinely testing Atlantic salmon for P. salmonis as part of a national control program. The panel of 14 samples included duplicates of three concentrations of P. salmonis in a homogenised head kidney, LF89 and EM90 bacteria and two negative controls (blank and a suspension of Flavobacterium psychrophilum ). The sample order was randomised across labs, samples were tested blinded and analysed without knowledge of the source lab. Of the laboratories, 8 (72.7%) had at least one incorrect result out of 14 tested samples. Low‐concentration samples ( C t of about 30) were more often incorrectly classified by reverse transcription‐qPCR (RT‐qPCR) (3/6 labs) than by qPCR (0/5). Six (54.5%) labs had at least one false‐positive result indicating that cross‐contamination was likely during sample processing. Affected laboratories are advised to conduct internal investigations to confirm the causes of false‐positive results and recommendations for design and implementation of future ring trials are discussed.

Whey draining of goat milk cheese: A model study using frontal filtration - Manon Basset; Julien Monteil; Valentin Demaille; Benjamin Faure; Fernando Leal-Calderon; Christelle Harscoat-Schiavo; Raphaëlle Savoire (Journal of Food Engineering, 2023)

Dietary inclusions of black soldier fly (Hermetia illucens) larvae frass enhanced production of channel catfish (Ictalurus punctatus) juveniles, stevia (Stevia rebaudiana), and lavender (Lavaridula angustifolia) in an aquaponic system - Nicholas Romano; Surjya Narayan Datta; Gde Sasmita Julyantoro Pande; Amit Kumar Sinha; Fernando Y. Yamamoto; Benjamin H. Beck; Carl D. Webster (Aquaculture, 2023)

Correction to: Feather stable isotopes (δ2 Hf and δ13Cf) identify the Sub-Saharan wintering grounds of turtle doves from Europe - Melanie Marx; Yvonne R. Schumm; Kevin J. Kardynal; Keith A. Hobson; Gregorio Rocha; Pavel Zehtindjiev; Dimitris Bakaloudis; Benjamin Metzger; Jacopo G. Cecere; Fernando Spina; Marco Cianchetti-Benedetti; Sylke Frahnert; et al. (European Journal of Wildlife Research, 2023)

High Temperature Tensile Strength of TI6AL4V Processed by L-PBF—Influence of Microstructure and Heat Treatment - Benjamin Meier; Fernando Warchomicka; Jelena Petrusa; Reinhard Kaindl; Wolfgang Waldhauser; Christof Sommitsch (BHM Berg- und Hüttenmännische Monatshefte, 2023)
Ti6Al4V is the most widely used α‑β Titanium alloy for application in medicine, automotive, and aerospace, known for its high strength and corrosion resistance, but also its high maximal operating temperature of around 420 °C. Combined with its decent weldability under a shield atmosphere it has become a standard alloy for additive manufacturing processes, especially laser and electron beam powder bed fusion (L-PBF). Although this material is well studied, the influence of the L‑PBF process on its tensile properties at elevated temperatures remains almost unexplored. For that reason, this contribution focuses on the analysis of the tensile properties of Ti6Al4V up to 500 °C for different heat treatments and compares it to aerospace standards. Furnace annealed samples reach a tensile strength between 1022 to 660 MPa from room temperature to 500 °C respectively, while stress-relieved specimens reach 1205 to 756 MPa. Stress-relieved samples show a lower ductility at room temperature, but elongation at break increases at high temperature and outperforms furnace annealed samples at 500 °C.

The genome sequence of the Neotropical brown stink bug, Euschistus heros provides insights into population structure, demographic history and signatures of adaptation - Kumar Saurabh Singh; Erick M.G. Cordeiro; Benjamin J. Hunt; Aniruddha A. Pandit; Patricia L. Soares; Alberto S. Correa; Christoph T. Zimmer; Maria I. Zucchi; Carlos Batista; Julian A.T. Dow; Shireen-Anne Davies; Fernando Luís Cônsoli; et al. (Insect Biochemistry and Molecular Biology, 2023)

The fall of the summer truffle: Recurring hot, dry summers result in declining fruitbody production of Tuber aestivum in Central Europe - Brian S. Steidinger; Ulf Büntgen; Uli Stobbe; Willy Tegel; Ludger Sproll; Matthias Haeni; Barbara Moser; István Bagi; José‐Antonio Bonet; Marc Buée; Benjamin Dauphin; Fernando Martínez‐Peña; et al. (Global Change Biology, 2022)
Global warming is pushing populations outside their range of physiological tolerance. According to the environmental envelope framework, the most vulnerable populations occur near the climatic edge of their species' distributions. In contrast, populations from the climatic center of the species range should be relatively buffered against climate warming. We tested this latter prediction using a combination of linear mixed effects and machine learning algorithms on an extensive, citizen‐scientist generated dataset on the fruitbody productivity of the Burgundy (aka summer) truffle ( Tuber aestivum Vittad . ), a keystone, ectomycorrhizal tree‐symbiont occurring on a wide range of temperate climates. T. aestivum 's fruitbody productivity was monitored at 3‐week resolution over up to 8 continuous years at 20 sites distributed in the climatic center of its European distribution in southwest Germany and Switzerland. We found that T. aestivum fruitbody production is more sensitive to summer drought than would be expected from the breadth of its species' climatic niche. The monitored populations occurring nearly 5°C colder than the edge of their species' climatic distribution. However, interannual fruitbody productivity (truffle mass year −1 ) fell by a median loss of 22% for every 1°C increase in summer temperature over a site's 30‐year mean. Among the most productive monitored populations, the temperature sensitivity was even higher, with single summer temperature anomalies of 3°C sufficient to stop fruitbody production altogether. Interannual truffle productivity was also related to the phenology of host trees, with ~22 g less truffle mass for each 1‐day reduction in the length of the tree growing season. Increasing summer drought extremes are therefore likely to reduce fruiting among summer truffle populations throughout Central Europe. Our results suggest that European T. aestivum may be a mosaic of vulnerable populations, sensitive to climate‐driven declines at lower thresholds than implied by its species distribution model.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Feather stable isotopes (δ2Hf and δ13Cf) identify the Sub-Saharan wintering grounds of turtle doves from Europe - Melanie Marx; Yvonne R. Schumm; Kevin J. Kardynal; Keith A. Hobson; Gregorio Rocha; Pavel Zehtindjiev; Dimitris Bakaloudis; Benjamin Metzger; Jacopo G. Cecere; Fernando Spina; Marco Cianchetti-Benedetti; Sylke Frahnert; et al. (European Journal of Wildlife Research, 2022)
Conservation of migratory birds requires knowledge of breeding and nonbreeding ranges and the connections between them. European turtle doves ( Streptopelia turtur ) are Palearctic-African long-distance migrants with wintering areas in the Sub-Saharan belt that are classed as vulnerable due to strong population declines. However, detailed non-breeding locations of individuals from different migratory flyways are unknown. To identify wintering regions of turtle doves, we measured stable isotopes of feathers grown on the wintering grounds and used a dual-isotope (hydrogen ( δ 2 H f ) and carbon ( δ 13 C f )) probabilistic assignment to analyse origins of individuals migrating through the western and central/eastern flyways. The most probable wintering areas for turtle dove samples from both flyways were in the western and central Sub-Sahara. However, we found differences in δ 2 H f and δ 13 C f values between turtle doves following different migratory routes (western vs central/eastern flyway). This result suggests a higher likelihood of origins in the central Sub-Sahara for central and eastern migrants, while turtle doves using the western flyway originated primarily in the western Sub-Sahara, highlighting the importance of both regions for the future conservation of turtle doves from European breeding populations. The establishment of migratory connectivity of populations requires sampling from birds from the European as well as Asian continent; however, we provide important results that can be used to test hypotheses regarding population declines resulting from factors experienced over the full annual cycle for some populations.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Correction to: Microphysics and Optical Attenuation in Fog: Observations from Two Coastal Sites - Qing Wang; Ryan T. Yamaguchi; John A. Kalogiros; Zachary Daniels; Denny P. Alappattu; Haflidi Jonsson; Oswaldo Alvarenga; Alex Olson; Benjamin J. Wauer; David G. Ortiz-Suslow; Harindra Joseph Fernando (Boundary-Layer Meteorology, 2021)

Microphysics and Optical Attenuation in Fog: Observations from Two Coastal Sites - Qing Wang; Ryan T. Yamaguchi; John A. Kalogiros; Zachary Daniels; Denny P. Alappattu; Haflidi Jonsson; Oswaldo Alvarenga; Alex Olson; Benjamin J. Wauer; David G. Ortiz-Suslow; Harindra Joseph Fernando (Boundary-Layer Meteorology, 2021)
A total of 15 fog events from two field campaigns are investigated: the High Energy Laser in Fog (HELFOG) project (central California) and the Toward Improving Coastal Fog Prediction (C-FOG) project (Ferryland Newfoundland). Nearly identical sensors were used in both projects to sample fog droplet-size spectra, wind, turbulence, and thermodynamic properties near the surface. Concurrent measurements of visibility were made by the present weather detector in both experiments, with the addition of a two-ended transmissometer in the HELFOG campaign. The analyses focused first on contrasting the observed fog microphysics and the associated thermodynamics from fog events in the two locations. The optical attenuation by fog was investigated using three methods: (1) derived from Mie theory using the measured droplet-size distribution, (2) parametrized as a function of fog liquid water content, and (3) parametrized in terms of total fog droplet number concentration. The consistency of these methods was investigated. The HELFOG data result in an empirical relationship between the meteorological range and liquid water content. Validation of such relationship is problematic using the C-FOG data due to the presence of rain and other factors. The parametrization with droplet number concentration only does not provide a robust visibility calculation since it cannot represent the effects of droplet size on visibility. Finally, a preliminary analysis of the mixed fog/rain case is presented to illustrate the nature of the problem to promote future research.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Simulation of stratified flows over a ridge using a lattice Boltzmann model - Yansen Wang; Benjamin T. MacCall; Christopher M. Hocut; Xiping Zeng; Harindra J. S. Fernando (Environmental Fluid Mechanics, 2020)
A three-dimensional thermal lattice Boltzmann model (TLBM) using multi-relaxation time method was used to simulate stratified atmospheric flows over a ridge. The main objective was to study the efficacy of this method for turbulent flows in the atmospheric boundary layer, complex terrain flows in particular. The simulation results were compared with results obtained using a traditional finite difference method based on the Navier–Stokes equations and with previous laboratory results on stably stratified flows over an isolated ridge. The initial density profile is neutral stratification in the boundary layer, topped with a stable cap and stable stratification aloft. The TLBM simulations produced waves, rotors, and hydraulic jumps in the lee side of the ridge for stably stratified flows, depending on the governing stability parameters. The Smagorinsky turbulence parameterization produced typical turbulence spectra for the velocity components at the lee side of the ridge, and the turbulent flow characteristics of varied stratifications were also analyzed. The comparison of TLBM simulations with other numerical simulations and laboratory studies indicated that TLBM is a viable method for numerical modeling of stratified atmospheric flows. To our knowledge, this is the first TLBM simulation of stratified atmospheric flow over a ridge. The details of the TLBM, its implementation of complex boundaries and the subgrid turbulence parameterizations used in this study are also described in this article.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Manufacturing of Pharmaceuticals by Impregnation of an Active Pharmaceutical Ingredient onto a Mesoporous Carrier: Impact of Solvent and Loading - Thamer A Omar; Sarang Oka; Fernando J. Muzzio; Benjamin J. Glasser (Journal of Pharmaceutical Innovation, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Biomarkers of Aryl-hydrocarbon Receptor Activity in Gulf Killifish (Fundulus grandis) From Northern Gulf of Mexico Marshes Following the Deepwater Horizon Oil Spill - Benjamin Dubansky; Charles D. Rice; Lester F. Barrois; Fernando Galvez (Archives of Environmental Contamination and Toxicology, 2017)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Are all seeds equal? Spatially explicit comparisons of seed fall and sapling recruitment in a tropical forest - Varun Swamy; John Terborgh; Kyle G. Dexter; Benjamin D. Best; Patricia Alvarez; Fernando Cornejo (Ecology Letters, 2011)
Ecology Letters (2011) 14: 195–201 Abstract Understanding demographic transitions may provide the key to explain the high diversity of tropical tree communities. In a faunally intact Amazonian forest, we compared the spatial distribution of saplings of 15 common tree species with patterns of conspecific seed fall, and examined the seed‐to‐sapling transition in relation to locations of conspecific trees. In all species, the spatial pattern of sapling recruitment bore no resemblance to predicted distributions based on the density of seed fall. Seed efficiency (the probability of a seed producing a sapling) is strongly correlated with distance from large conspecific trees, with a > 30‐fold multiplicative increase between recruitment zones that are most distant vs. proximal to conspecific adults. The striking decoupling of sapling recruitment and conspecific seed density patterns indicates near‐complete recruitment failure in areas of high seed density located around reproductive adults. Our results provide strong support for the spatially explicit predictions of the Janzen–Connell hypothesis.

Decreasing resilience of kelp beds along a latitudinal temperature gradient: potential implications for a warmer future - Thomas Wernberg; Mads S. Thomsen; Fernando Tuya; Gary A. Kendrick; Peter A. Staehr; Benjamin D. Toohey (Ecology Letters, 2010)
Ecology Letters (2010) 13: 685–694 Abstract Successful mitigation of negative effects of global warming will depend on understanding the link between physiological and ecological responses of key species. We show that while metabolic adjustment may assist Australasian kelp beds to persist and maintain abundance in warmer waters, it also reduces the physiological responsiveness of kelps to perturbation, and suppresses canopy recovery from disturbances by reducing the ecological performance of kelp recruits. This provides a warning not to rely solely on inventories of distribution and abundance to evaluate ecosystem function. The erosion of resilience is mediated by a shift in adult‐juvenile interactions from competitive under cool to facilitative under warm conditions, supporting the prediction that positive interactions may become increasingly important in a warmer future. Kelp beds may remain intact but with a lower threshold for where additional impacts (e.g., extreme storms or reduced water quality) will lead to persistent loss of habitat and ecological function.

Understanding movement data and movement processes: current and emerging directions - Robert S. Schick; Scott R. Loarie; Fernando Colchero; Benjamin D. Best; Andre Boustany; Dalia A. Conde; Patrick N. Halpin; Lucas N. Joppa; Catherine M. McClellan; James S. Clark (Ecology Letters, 2008)
Animal movement has been the focus on much theoretical and empirical work in ecology over the last 25 years. By studying the causes and consequences of individual movement, ecologists have gained greater insight into the behavior of individuals and the spatial dynamics of populations at increasingly higher levels of organization. In particular, ecologists have focused on the interaction between individuals and their environment in an effort to understand future impacts from habitat loss and climate change. Tools to examine this interaction have included: fractal analysis, first passage time, Lévy flights, multi‐behavioral analysis, hidden markov models, and state‐space models. Concurrent with the development of movement models has been an increase in the sophistication and availability of hierarchical bayesian models. In this review we bring these two threads together by using hierarchical structures as a framework for reviewing individual models. We synthesize emerging themes in movement ecology, and propose a new hierarchical model for animal movement that builds on these emerging themes. This model moves away from traditional random walks, and instead focuses inference on how moving animals with complex behavior interact with their landscape and make choices about its suitability.

Efficient in vitro propagation of Agave parrasana Berger - Fernando Santacruz-Ruvalcaba; Humberto Gutiérrez-Pulido; Benjamin Rodríguez-Garay (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)